Assignment of the locus for a new lethal neonatal metabolic syndrome to 2q33-37. - Visapää, I (1998)
A new neonatal syndrome characterized by intrauterine growth retardation, lactic acidosis, aminoaciduria, liver hemosiderosis, and early death was recently described. The pathogenesis of this disease is unknown. The mode of inheritance is autosomal recessive, and so far only 17 cases have been reported in 12 Finnish families. Here we report the assignment of the locus for this new disease to a restricted region on chromosome 2q33-37. We mapped the disease locus in a family material insufficient for traditional linkage analysis by using linkage disequilibrium, a possibility available in genetic isolates such as Finland. The primary screening of the genome was performed with samples from nine affected individuals in five families. In the next step, conventional linkage analysis was performed in eight families, with a total of 12 affected infants, and finally the locus assignment was proved by demonstrating linkage disequilibrium to the regional markers in 20 disease chromosomes. Linkage analysis restricted the disease locus to a 3-cM region between markers D2S164 and D2S2359, and linkage disequilibrium with the ancestral haplotype restricted the disease locus further to the immediate vicinity of marker D2S2250.